Are returns to public investment lower in less-favored rural areas?: an empirical analysis of India - Fan, Shenggen; Hazell, Peter B. R. (International Food Policy Research Institute, 1999)
Developing countries allocate scarce government funds to investments in rural areas to achieve the twin goals of agricultural growth and poverty alleviation. Choices have to be made between different types of investments, especially infrastructure, human capital and agricultural research, and between different types of agricultural regions, e.g., irrigated and high- and low-potential rainfed areas. This paper develops an econometric approach and provides empirical evidence on the impact of government investments in rural India using district-level data. While irrigated areas played a key role in agricultural growth during the Green Revolution era, our results show that it is now the rainfed areas, including many less-favored areas that offer the most growth for an additional unit of investment. Moreover, investments in rainfed areas have a much larger impact on poverty alleviation, making this a win-win development strategy. These results have important policy implications, and challenge conventional thinking that public investments in rural India should always be targeted to irrigated and other high-potential areas.